Epidermal systems and virtual reality: Emerging disruptive technology for military applications - Marsili, M. (Key Engineering Materials, 2021)
This review study, presented at the 2nd World Conference on Advanced Materials for Defense (AuxDefense 2020), focuses on skin as sensory interface and explores the latest discoveries in bioelectronic science. The work analyzes at what extent invisibility is possible by emulating nature, and if military applications can really benefit from technology that combines epidermal systems and virtual reality — and from next generation of wearable textile computing technologies.